2021
DOI: 10.1177/09636897211067454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Imaging Outcomes of Different Doses of Adipose-Derived Stromal Vascular Fraction Cell Treatment for Knee Osteoarthritis

Abstract: Favorable clinical outcomes of intra-articular injection of adipose-derived stromal vascular fraction (SVF) cells for knee osteoarthritis (OA) have been reported, but the effects of different doses of SVF cells have not been examined. This study aimed to compare the short-term clinical and imaging outcomes of different doses of SVF cells for knee OA treatment. This study included 60 patients with knee OA who underwent intra-articular injection of SVF cells. The follow-up period was at least 12 months. Thirty p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…All the included studies used autologous-derived MSCs. Seven studies used MSCs provided by the abdominal adipose tissue [ 1 , 10 , 21 , 27 29 ], four used bone marrow from the iliac crest [ 2 , 7 , 22 , 24 ], and one from both sources [ 3 ]. Different reported devices were used for harvesting adipose or bone marrow-derived MSCs (Celution, Lipogems, Lipocell, GID SVF-2, PureBMC) [ 2 , 8 , 10 , 21 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included studies used autologous-derived MSCs. Seven studies used MSCs provided by the abdominal adipose tissue [ 1 , 10 , 21 , 27 29 ], four used bone marrow from the iliac crest [ 2 , 7 , 22 , 24 ], and one from both sources [ 3 ]. Different reported devices were used for harvesting adipose or bone marrow-derived MSCs (Celution, Lipogems, Lipocell, GID SVF-2, PureBMC) [ 2 , 8 , 10 , 21 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, almost all studies have shown shortterm clinical outcomes, and thus the interpretation of these results should be made cautiously. One of the studies showed the K-L grade 2 and 3 OA results separately and demonstrated more remarkable progress in the case of grade 2 arthritis which was predictable [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, other authors reported positive correlations between SVF‐based treatment outcomes and the number of SVF cells. Tsubosaka et al [38] compared the 12‐month outcomes of 60 patients; 30 received an intra‐articular injection with 2.5 × 10 7 SVF cells (low‐dose group), and 30 received an intra‐articular injection of 5.0 × 10 7 SVF cells (high‐dose group). They reported that the 12‐month postoperative pain and symptom subscale KOOS scores were significantly better in the high‐dose group than in the low‐dose group.…”
Section: Discussionmentioning
confidence: 99%
“…Pain decreased and function improved in those patients with time. The effectiveness of the intra-articular injection of SVF could be cell-dose dependent [ 168 ]. The higher dose had better outcomes in 60 patients.…”
Section: Adipose Derived Stromal Vascular Fraction (Ad-svf)mentioning
confidence: 99%